Persepsi, Ketertarikan, Dan Kebutuhan: Mengukur Minat Siswa Terhadap Bola Voli Di Lingkungan Terbatas - Jamaliah, Naimatul Jamaliah; Syatiri, Muhammar; Zulfikri, Zulfikri (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2025)
This study aims to analyze students' interest in volleyball and evaluate three factors that influence it: interest, attention, and need. A descriptive quantitative approach was used with a total sampling technique on 61 students at Al Umm Smart Center Islamic Junior High School. The instrument, consisting of a 17-item questionnaire, was validated through expert judgment and tested for reliability using Cronbach's Alpha (α = 0.921). Data analysis was conducted descriptively through frequency distribution and score categorization. The results showed that overall student interest was in the high category, with 52% of students having very high interest, 28% high interest, and 20% low interest. The dimension of need received the highest average score, followed by attention and interest. Students viewed volleyball as a means of self-development, social interaction, and actualization, despite still facing obstacles such as limited facilities and environmental support. Supportive learning, teacher quality, and pedagogical strategies proved to play an important role in shaping student interest. These findings confirm the relevance of the Self-Determination Theory (SDT) and Expectancy-Value Theory (EVT) approaches in understanding student motivation towards sports. This study recommends improving teacher competence, providing facilities, and developing community-based and locally cultural sports programs. Further research is suggested to explore the role of cultural and gender factors in developing interest in sports at school